1998
DOI: 10.1164/ajrccm.158.5.9802035
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking in HIV Infection Induces a Suppressive Inflammatory Environment in the Lung

Abstract: Lung lymphocyte numbers are frequently increased in human immunodeficiency virus (HIV)-infected individuals in the absence of lung infection, and may play a critical role in viral surveillance and protection against new infections. In this context, cigarette smoking by HIV-infected individuals has been associated with a relative increase in the peripheral blood CD4(+) T-lymphocyte count as compared with that of nonsmokers. Because lung defense is local, the aim of the present study was to determine whether cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 29 publications
0
47
2
1
Order By: Relevance
“…Airways and lung parenchyma. Bronchoalveolar lavage studies have demonstrated a marked decrease in the absolute number of CD4+ cells, and an increase in CD8+ cells with a lower CD4+/CD8+ cell ratio in moderate smokers vs nonsmokers (Leatherman et al, 1984;Costabel et al, 1986;Wewers et al, 1998). No significant changes in these variables in the peripheral blood were found in this population of moderate smokers, in contrast with the www.intechopen.com Bronchitis 70 findings in heavy smokers discussed previously.…”
Section: Cell-mediated Immune Responsesmentioning
confidence: 54%
“…Airways and lung parenchyma. Bronchoalveolar lavage studies have demonstrated a marked decrease in the absolute number of CD4+ cells, and an increase in CD8+ cells with a lower CD4+/CD8+ cell ratio in moderate smokers vs nonsmokers (Leatherman et al, 1984;Costabel et al, 1986;Wewers et al, 1998). No significant changes in these variables in the peripheral blood were found in this population of moderate smokers, in contrast with the www.intechopen.com Bronchitis 70 findings in heavy smokers discussed previously.…”
Section: Cell-mediated Immune Responsesmentioning
confidence: 54%
“…(21) This difference between HIV-infected patients and the general population has been reported in other studies in which the prevalence of HIV+ smokers ranged from 31% to 88%. (22)(23)(24) This high prevalence might be related to the great number of people with a history of illicit drug use, which has been strongly correlated with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that smoking among HIV+ people would be associated with markers of HIV disease progression (e.g., CD4 count, viral load). There is mixed support for the association between smoking and a decrease in CD4 count, with some research suggesting that there is no association (Gritz et al, 2004), and other studies finding decrements in CD4 counts as a function of smoking status (Royce & Winkelstein, 1990;Wewers et al, 1998). In a large-scale longitudinal study, Feldman et al (2006) found that HIV+ female smokers -who were prescribed antiretroviral therapy (HAART) -had poorer immunologic and viral responses.…”
Section: High Smoking Prevalence Among Hiv+ Men and Women: Examining mentioning
confidence: 99%